Development of Wind Direction and Speed Monitoring with Solar Power in Airport Study Learning - Soleh, Asep Muhamad; Sukahir; Widiarto, Hendro; Kusumastuti, Mayang Enggar (Jurnal Ilmu Dan Rekayasa Sipil, 2024)
Monitoring weather conditions, particularly wind direction and speed, is a crucial aspect of airport operations as it impacts flight safety, fuel efficiency, and flight schedules. This study aims to develop a solar-powered wind direction and speed monitoring system as a learning medium for cadets at Palembang Aviation Polytechnic. The system is designed to be portable and environmentally friendly, enabling deployment in various locations without reliance on conventional power sources. This research employs the research and development (R&D) method using the Borg & Gall model, encompassing the stages of needs analysis, design, development, testing, and evaluation. The results indicate that cadets are enthusiastic about learning and developing this tool. The use of wind direction and speed indicators displayed on a Liquid Crystal Display (LCD) screen facilitates real-time data reading. Testing revealed a significant improvement in cadets' understanding and skills after using this learning medium, as demonstrated by pre-test and post-test results. With this learning medium, cadets are expected to understand the principles of the tool's operation, maintain it, and further develop wind direction and speed indicators in their future workplaces. This innovation is anticipated to enhance the quality of aviation education and contribute to improved aviation safety in Indonesia.